2006
DOI: 10.1063/1.2424653
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of Ohmic contacts to ZnSe nanowires and their application to nanowire-based photodetection

Abstract: Multilayer Ti∕Au contacts were fabricated on individual, unintentionally doped zinc selenide nanowires with 80nm nominal diameter. Four-terminal contact structures were used to independently measure current-voltage characteristics of contacts and nanowires. Specific contact resistivity of Ti∕Au contacts is 0.024Ωcm2 and intrinsic resistivity of the nanowires is approximately 1Ωcm. The authors have also measured the spectral photocurrent responsivity of a ZnSe nanowire with 2.0V bias across Ti∕Au electrodes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 16 publications
1
68
0
Order By: Relevance
“…11 It has been proposed by theory that Fermi level pinning effects, which frequently hinder the performance of planar devices, 12 are expected to be strongly reduced in side contacts to NW channels due to their confined geometry. 13,14 Although several studies regarding the contact-resistivity in semiconducting NW devices can be found, [6][7][8][9][10] an analysis addressing both the contact-interface properties and also verifying the plausibility of common bulk-based extrapolation methods is to-date not presented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 It has been proposed by theory that Fermi level pinning effects, which frequently hinder the performance of planar devices, 12 are expected to be strongly reduced in side contacts to NW channels due to their confined geometry. 13,14 Although several studies regarding the contact-resistivity in semiconducting NW devices can be found, [6][7][8][9][10] an analysis addressing both the contact-interface properties and also verifying the plausibility of common bulk-based extrapolation methods is to-date not presented.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Properties of electrode/NW contact-interfaces are of particular interest [6][7][8][9][10] due to the potential application of quasi-one-dimensional materials into future nanosensing and nanoelectronic devices. 11 It has been proposed by theory that Fermi level pinning effects, which frequently hinder the performance of planar devices, 12 are expected to be strongly reduced in side contacts to NW channels due to their confined geometry.…”
mentioning
confidence: 99%
“…We observed linear current-voltage characteristics with a typical resistivity of 1 O-cm which is comparable to that of unintentionally-doped n-type ZnSe thin films [7]. The specific conatct resistivity was extracted using a modified transmission line model to be 0.024 comparable to similar contacts in bulk ZnSe samples.…”
Section: Single Nanowire Photoconductormentioning
confidence: 93%
“…Various techniques of contacting nanowires have been demonstrated by placing an individual nanowire across pre-fabricated metal electrodes on an insulating surface, or alternatively, placing an individual nanowire on an insulating surface and then, putting down a pair of electrodes onto the nanowire. 114,115 Apparently, these methods are not favorable to establishing reliable electrical contacts at large wafer scale. Nanowires bridging across a gap between semiconductor electrodes have also been demonstrated for silicon and III-V compound semiconductors, 116,117,118 in which single-crystal substrates were used.…”
Section: Building Blocks For Nanowire Solid-state Devicesmentioning
confidence: 99%